Structural Information and Communication Complexity 18th International Colloquium, SIROCCO 2011, Gdańsk, Poland, June 26-29, 2011: proceedings - Colloquium on structural information and communication complexity Gdansk, Poland) 2011; Kosowski, Adrian; Yamashita, Masafumi (Berlin, Heidelberg New York Springer, 2011)
This book constitutes the refereed proceedings of the 18th International Colloquium on Structural Information and Communication Complexity, SIROCCO 2011, held in Gdańsk, Poland, in June 2011. The 24 revised full papers presented together with 1 survey lecture and 2 invited talks were carefully reviewed and selected from 57 submissions.
Keywords: Electronic data processing -- Distributed processing. -- Congresses; Computer algorithms -- Congresses; Computer networks -- Congresses